Constipation in patients with myofascial pain syndrome as important aspect for clinical and nutritional treatment: A case-control study - Formiga Cavalcanti de LIMA, Rafaela Lira (2023)
ObjectiveTo identify the occurrence of constipation in patients with myofascial pain syndrome and to correlate these disorders with the clinical and nutritional variables. MethodsThis report describes a case-control study performed with 98 adults of both sexs, including 49 patients and 49 individuals without pain. The intensity of the reported pain was evaluated using the Pain Visual Analog Scale, which provided a simple and efficient measurement of pain intensity consisting of a 10cm horizontal line withthe ends marked “absence of pain” and “worst possible pain”. The occurrence of constipation was evaluated using the Rome III criteria. A multivariate linear regression was proposed to investigate risk factors between the frequency of bowel movements per week and independent variables this study. ResultsThe mean ages of the patients and controls were 45.9 (7.6) years and 41.2 (12.2) years, respectively. The intensity of the reported pain showed a mean of 7.3 (1.6) points. The likelihood of exhibiting constipation was 4.5 times higher in the patients than in the controls (p=0.001). The number of stools per week was negatively correlated with the intensity of the reported pain (r=-0.613, p<0.001). The use of benzodiazepines was negatively correlated with the frequency of bowel movements per week, while the use of muscle relaxants appeared to increase the frequency of defecation when combined with the use of benzodiazepines and adjusted for the intake of fiber, water and sexs (p=0.037). ConclusionConstipation was a frequent nosological entity in this patient population and the persistence of a change in intestinal motility showed a significant correlation with the pain intensity and low water intake. The reduction of the number of stools per week seems to be associated with the use of benzodiazepines.